Risk Factors of Ischemic and Hemorrhagic Strokes During Venovenous Extracorporeal Membrane Oxygenation: Analysis of Data From the Extracorporeal Life Support Organization Registry - Cho, Sung-Min; Canner, Joe; Caturegli, Giorgio; Choi, Chun Woo; Etchill, Eric; Giuliano, Katherine; Chiarini, Giovanni; Calligy, Kate; Rycus, Peter; Lorusso, Roberto; Kim, Bo Soo; Sussman, Marc; et al. (Critical care medicine, 2021)
Stroke is commonly reported in patients receiving venovenous extracorporeal membrane oxygenation, but risk factors are not well described. We sought to determine preextracorporeal membrane oxygenation and on-extracorporeal membrane oxygenation risk factors for both ischemic and hemorrhagic strokes in patients with venovenous extracorporeal membrane oxygenation support. Retrospective analysis. Data reported to the Extracorporeal Life Support Organization by 366 extracorporeal membrane oxygenation centers from 2013 to 2019. Patients older than 18 years supported with a single run of venovenous extracorporeal membrane oxygenation. None. Of 15,872 venovenous extracorporeal membrane oxygenation patients, 812 (5.1%) had at least one type of acute brain injury, defined as ischemic stroke, hemorrhagic stroke, or brain death. Overall, 215 (1.4%) experienced ischemic stroke and 484 (3.1%) experienced hemorrhagic stroke. Overall inhospital mortality was 36%, but rates were higher in those with ischemic or hemorrhagic stroke (68% and 73%, respectively). In multivariable analysis, preextracorporeal membrane oxygenation pH (adjusted odds ratio = 0.10; 95% CI, 0.03-0.35; p < 0.001), hemolysis (adjusted odds ratio = 2.27; 95% CI, 1.22-4.24; p = 0.010), gastrointestinal hemorrhage (adjusted odds ratio = 2.01; 95% CI 1.12-3.59; p = 0.019), and disseminated intravascular coagulation (adjusted odds ratio = 3.61; 95% CI, 1.51-8.66; p = 0.004) were independently associated with ischemic stroke. Pre-extracorporeal membrane oxygenation pH (adjusted odds ratio = 0.28; 95% CI, 0.12-0.65; p = 0.003), preextracorporeal membrane oxygenation Po2 (adjusted odds ratio = 0.96; 95% CI, 0.93-0.99; p = 0.021), gastrointestinal hemorrhage (adjusted odds ratio = 1.70; 95% CI, 1.15-2.51; p = 0.008), and renal replacement therapy (adjusted odds ratio=1.57; 95% CI, 1.22-2.02; p < 0.001) were independently associated with hemorrhagic stroke. Among venovenous extracorporeal membrane oxygenation patients in the Extracorporeal Life Support Organization registry, approximately 5% had acute brain injury. Mortality rates increased two-fold when ischemic or hemorrhagic strokes occurred. Risk factors such as lower pH and hypoxemia during the pericannulation period and markers of coagulation disturbances were associated with acute brain injury. Further research on understanding preextracorporeal membrane oxygenation and on-extracorporeal membrane oxygenation risk factors and the timing of acute brain injury is necessary to develop appropriate prevention and management strategies.